DEVELOPMENT AND VALIDATION OF THE TOXIC POSITIVITY SCALE - Fathimah Aulia Rahma; Haifa Ersa Salsabila; Nurfitriani Khofifah; Saeful Rachman; Siti Khansa A. Firdaus; Naera Zhafira Azkiati Zamzami; Novita Sari (International Journal of Social Science, 2026)
A This study aims to develop and validate a measurement instrument based on Goodman’s (2022) theory. A quantitative approach was employed, utilizing 22 developed items of toxic positivity to verify the three aspects according to Whitney Goodman’s theory. The research sample consisted of 205 participants. The sampling technique used was convenience sampling, categorized under non-probability sampling. Data analysis involved several tests, including content validity using Aiken’s V, prerequisite testing via KMO and Bartlett’s tests, Exploratory Factor Analysis (EFA), and reliability testing using Cronbach’s Alpha. The Aiken’s V analysis, involving 6 raters and a 5-point scale, yielded a value of 0.77. The results of the data feasibility test using Kaiser-Meyer-Olkin (KMO) showed a value of 0.780, which falls within the "fairly good" category. The EFA revealed a consistent three-factor structure: Invalidation of Emotion, Shame Disguised, and Denial. Furthermore, the Cronbach’s Alpha reliability test yielded a coefficient of 0.791, indicating that the instrument possesses good internal consistency and is suitable for use. Consequently, 11 items were identified as valid for measuring toxic positivity. This scale is an appropriate instrument for measuring toxic positivity behavioral tendencies. The implication of this study is the availability of a validated psychological measurement tool to identify patterns of toxic positivity.